The Great Ocean Conveyor : Discovering the Trigger for Abrupt Climate Change - Broecker, Wallace S., 1931-2019 (Book collections on Project MUSE., 2010)
This title explores the realization that the Earth's climate system could undergo abrupt reorganizations, changing temperatures and rainfall across much of the planet.